World Anthropology Day – Antropologia pubblica a Milano. Una piattaforma strategica per porre la Terza Missione al centro - Bargna, Leopoldo Ivan (Antropologia Pubblica, 2024)
Enhancing cultural diversity is key to deal with change and innovation in socially sustainable ways. “World Anthropology Day – Antropologia pubblica a Milano” is an incubator for integrating anthropological knowledge, social and professional know-how, starting from effective collaborative experiences carried out all over the town, and presented where they took place with the people who participated in them. It is a platform for networking academic and professional anthropologists, the world of work, third sector and the city as a whole, allowing to rethink research and public engagement in their mutual implications, generating new transformative projects and favoring a realignment between the social perception of what anthropologists are and what they actually do. The university coordinates the initiative, but all events are organized independently by those who have leaded them, enhancing autonomy. Territorial roots are combined with mobility routes, proposing projects born in Milan and moved elsewhere, or arriving and passing from there: proximity passes from neighborhood relations, as well as from connections with the world. On this basis, public engagement can become an integral part of research and teaching in real-life contexts as well.